PENGETAHUAN POLA MAKAN PASIEN DIABETES MELLITUS DI WILAYAH KERJA UPTD PUSKESMAS NANGA MAU TAHUN 20 - Herman, Joni (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2023)
Diabetes mellitus is a disease caused by the failure of the breakdown of sugar in the body (blood) in a normal body. The number of diabetes mellitus cases at the Nanga Mau Community Health Center was 71 cases. The aim of the research was to determine the knowledge of the diet of diabetes mellitus patients in the UPTD Working Area of ​​the Nanga Mau Health Center. The type of research used was descriptive quantitative with a cross sectional research design. The total population and sample were 71 respondents. The analysis used is univariate. The research results showed that respondents with good knowledge were 15 or 21%, while respondents with less knowledge were 56 or 79%. Conclusion: Respondents' knowledge about diabetes mellitus at the Nanga Mau Community Health Center is still lacking. Advice is to maintain your diet, avoid foods that are high in glucose and regularly measure blood sugar to determine blood sugar levels.